Commissions for the study of the violence in colombia. the "critical voice" one of their protagonists (interview with historian gonzalo sanchez) (2011)
In this interview, Professor Gonzalo Sánchez offers testimony on the impact for Colombia and for the social sciences of two commissions to study violence in the country (the Second Committee for the Study of Violence (1987) and Historical Memory Group, National Commission for Reparation and Reconciliation. With his academic vision and as part of these committees, Professor Sánchez addresses issues such as memory, truth, justice and the victims in the context of the conflict.